(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
In this paper we investigate the causal relationship between R&D cooperation and economic growth. We use an innovative econometric method which is based on a panel test of the Granger non causality hypothesis. We implement various tests with a sample of 32 industrial and developing countries over the 1970-2012 periods. The results provide support for a robust causality relationship from economic growth to the R&D cooperation. On the contrary, the non causality hypothesis from R&D cooperation to economic growth can’t be rejected in most of the cases. However, these results only imply that, if such a relationship exists, it can’t be easily identified in a simply bi-variate Granger causality test.